Tolerance to freezing stress in cyanobacteria, Nostoc commune and some cyanobacteria with various tolerances to drying stress - Lin, Yufang; Hirai, Manabu; Kashino, Yasuhiro; Koike, Hiroyuki; Tuzi, Satoru; Satoh, Kazuhiko (National Institute of Polar Research, 2004)
P(論文) Tolerance to and effects of the freezing stress in a desiccation-tolerant, terrestrial cyanobacterium, Nostoc commune, in cultivated strains of N. commune, and in desiccation-sensitive species, Synechocystis sp. PCC6803 and Fischerella muscicola, were studied by measuring their photosynthetic activities and fluorescence emission spectra. The results showed that a strain or species with higher desiccation tolerance was more tolerant to freezing stress than one with lower desiccation tolerance, which is consistent with the idea that tolerance to freezing stress is related to resistance to drying stress. Under freezing conditions, light energy absorbed by photosystem (PS) II complexes was dissipated to heat energy in N. commune, which may protect the cells from photoinactivation. N. commune encountered cellular dehydration due to ice formation outside the cell under freezing conditions. But NMR data showed that relatively high amounts of water still remained in a liquid state inside the cells at -36_C when N. commune colonies were fully wetted before freezing. High PSI activities measured by P700 photooxidation also support the result that non-freezing water remains within the cells. Besides, 5% methanol enhanced the resistance to freezing stress in the sensitive species. This effect seems to be related to maintenance of the PSI activity and pigment-protein complexes in their functional forms by methanol. departmental bulletin paper